Ritual Pemakaman Turunan Bokeo di Kelurahan Silea Kecamatan Wundulako Kabupaten Kolaka - Runni Yanti Mansur; Laxmi Laxmi (JURNAL KABANTI: Kerabat Antropologi, 2024)
This study aims to determine the funeral ritual procession of Bokeo derivatives in Silea Village, Wundulako District, Kolaka Regency. This research uses Levi-Strauss (1958) Structural Theory Attitude of Relationship Between Relatives Elementally. The data collection technique used in this research is Snowball Sampling by conducting involved observation (observation participation) and in-depth interviews. this research is Qualitative research using Ethnographic research methods. The research shows that: first: when a bokeo descendant dies, several funeral ritual processes will be carried out, namely first; making a coffin from the trunk of an areca tree (pu'umbundi), second; wearing forty sarongs as a calendar (O'sawu), third; slaughtering buffaloes (To'ono Mogere) and fourth; funeral custom umbrella (O'pawu).